IMPORTANCE OF MEDIA EDUCATION IN WORKING WITH STUDENTS - Alimova Qunduz Oybek qizi (Journal of new century innovations, 2022)
Abstract: This article contains information about the importance of media education in working with students and the impact of mass media on the educational process and social and political activities today.